Recycling to Save Lives: Making Manikins from Recyclable Materials for Cardiopulmonary Resuscitation Training - Gozuen, Verediana Freitas; Marques, Youry Souza; Pereira, Noriel Viana (International Journal for Innovation Education and Research, 2020)
Introduction: Cardiopulmonary Arrest (CPA) is a global public health problem and, for this reason, once it is identified, early Cardiopulmonary Resuscitation (CPR) must be initiated and effectively carried out in order to improve the victim´s prognosis. Objective: The objective of the project was to train students and civil servants from a public university in order to promote their interaction with the population assisted by the DIST/Shopping Park program through workshops on making recyclable manikins; training on Cardiopulmonary Arrest (CPA) identification and Cardiopulmonary Resuscitation. Methodology: The RECYCLE TO SAVE LIVES - CPR project was an activity promoted by the Federal University of Uberlandia (UFU), in 2018, which associated environment with health promotion and education and encouraged the initial training of 28 people to serve as volunteers in the external community of the University, 44 people from different age groups then received a similar training through workshops. Result: The project approach was efficient, as it managed to associate theory with practice, through the use of the recyclable manikins. However, it was found that health education activities need to be more present in educational environments, and not just at specific moments of intervention, as proposed by the project, as we assume that over time, theoretical and practical knowledge might be forgotten. Conclusion: The project achieved good results with the training offered through workshops, and while working directly with the community it played a significant role of social intervention, which is one of the responsibilities of the University.